A compound containing a nitrogen heterocyclic structure and an organic electroluminescent device
By designing compounds containing nitrogen heterocyclic structures and cooperating them with P-type compounds to form Premix materials, the problem of poor matching between green light bodies of OLED devices is solved, the stability and life of the device are improved, and the luminous efficiency is enhanced.
Patent Information
- Application Number
- CN202411624923.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The poor matching of existing OLED devices between green light bodies, resulting in inefficient energy transfer, reduced conductor efficiency, and poor chemical, thermal and photoelectric stability of the materials, affecting the device life and stability.
A class of compounds containing nitrogen heterocyclic structures were designed and combined with P-type compounds to form a Premix material. The chemical, thermal and photoelectric stability of the compounds were improved by deuterated active sites, and an organic electroluminescent material with equilibrium carrier mobility was formed.
It improves the stability and life of the device, enhances the luminous efficiency, reduces the starting voltage and power consumption, and improves the stability of mass production.
Smart Images

Figure CN119161330B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic electroluminescence, and in particular to a compound and an organic electroluminescence device. Background Art
[0002] Organic electroluminescence usually refers to an organic light-emitting diode (OLED) that uses electric current to drive an organic semiconductor film to emit light, thereby achieving the purpose of display.
[0003] The composition structure of an organic electroluminescent device includes a cathode, an anode, and an organic layer disposed therebetween. The organic layer structure of OLED devices currently used in the industry is usually a multilayer structure, for example, including a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, an electron injection layer and other film layers. For an OLED device including the above-mentioned film layers, when a voltage is applied between the two electrodes, holes are injected from the anode into the organic layer, and electrons are injected from the cathode into the organic layer. When holes and electrons meet, excitons are formed. When the excitons transfer energy to the doping material, light is emitted through the radiation transition of the doping material.
[0004] In existing OLED devices, due to the poor compatibility between green light hosts, energy cannot be efficiently transferred to doping materials, and the efficiency of conductive OLED devices has decreased. At the same time, since it has not been deuterated at the active sites and sites with high electron density of the material molecules, its chemical stability, thermal stability and photoelectric stability are poor, which in turn affects the life of the device. In addition, the P / N ratio of the current green light host will change greatly with the extension of the evaporation time, resulting in large fluctuations in device performance, poor stability and low yield.
[0005] The premix material formed by the combination of the N-type compound and the P-type compound of the present invention has good thermal stability, chemical stability and photoelectric stability because the active sites of their respective structures are deuterated. At the same time, the premix material formed by the compounds of the present invention has a balanced carrier mobility, further widens the exciton recombination area, and thus improves the life and efficiency of the device. Summary of the invention
[0006] The purpose of the present invention is to provide a compound containing a nitrogen heterocyclic structure and an organic electroluminescent device based on the prior art.
[0007] The purpose of the present invention can be achieved by the following measures:
[0008] A compound containing a nitrogen heterocyclic structure, the structural formula of which is shown in Formula 1 below:
[0009]
[0010] Y is O or S;
[0011] X1-X3 are each independently selected from N or CR1, and at least one of X1-X3 is N;
[0012] Ar is selected from the following substituted or unsubstituted groups: phenyl, biphenyl, terphenyl, naphthyl, phenanthryl, triphenylene, anthracenyl, pyridyl, pyrimidyl, triazine, dibenzofuranyl, dibenzothienyl, carbazolyl, fluorenyl, spirobifluorenyl, and the substituent of Ar is deuterium, fluorine, cyano, deuterated or undeuterated groups: phenyl, biphenyl, naphthyl, pyridyl, methyl, ethyl, tert-butyl, cyclopentyl, cyclohexyl or one or more thereof;
[0013] L1-L2 are each independently selected from a single bond, a substituted or unsubstituted phenyl group, a substituted or unsubstituted biphenyl group, and the substituents of L1-L2 are selected from one or more of deuterium, fluorine, cyano, C1-C10 alkyl, C6-C18 aryl, and C5-C20 heteroaryl;
[0014] R is independently selected from hydrogen, deuterium, fluorine, cyano, deuterated or undeuterated groups: phenyl, biphenyl, methyl, ethyl, tert-butyl, or one or more thereof;
[0015] A1-A8 are each independently selected from deuterium or phenyl, and not all of A1-A8 are deuterium;
[0016] R1 is selected from hydrogen, deuterium, fluorine, deuterated or undeuterated groups: methyl, ethyl, tert-butyl, phenyl, biphenyl;
[0017] R2 is hydrogen or deuterium;
[0018] n is an integer from 0 to 6;
[0019] m is 0 or 5.
[0020] In a preferred embodiment, the structural formula is shown in Formulas 2 and 3 below:
[0021] ;
[0022] Y is O or S;
[0023] X1-X3 are each independently selected from N or CR1, and at least one of X1-X3 is N;
[0024] Ar is selected from the following substituted or unsubstituted groups: phenyl, biphenyl, terphenyl, naphthyl, phenanthrenyl, triphenylene, anthracenyl, pyridyl, pyrimidinyl, triazine, dibenzofuranyl, dibenzothiophenyl, wherein the substituent of Ar is deuterium, fluorine, cyano, deuterated or undeuterated groups: phenyl, biphenyl, methyl, ethyl, tert-butyl, cyclopentyl, cyclohexyl or one or more thereof;
[0025] L1-L2 are each independently selected from a single bond, phenyl, deuterated phenyl, biphenyl, deuterated biphenyl, and pyridyl;
[0026] R is independently selected from hydrogen, deuterium, fluorine, cyano, deuterated or undeuterated groups: phenyl, biphenyl, methyl, ethyl, tert-butyl, or one or more thereof;
[0027] A1-A8 are each independently selected from deuterium or phenyl, and not all of A1-A8 are deuterium;
[0028] R1 is selected from hydrogen, deuterium, fluorine, deuterated or undeuterated groups: methyl, ethyl, tert-butyl, phenyl, biphenyl;
[0029] n is an integer from 0 to 6.
[0030] Further preferably, its structural formula is shown in Formula 4 and 5 below:
[0031] ;
[0032] Y is O or S;
[0033] Ar is selected from the following substituted or unsubstituted groups: phenyl, biphenyl, terphenyl, and the substituent of Ar is deuterated, deuterated or undeuterated following groups: one or more of phenyl and biphenyl;
[0034] R is independently selected from hydrogen, deuterium, fluorine, cyano, deuterated or undeuterated groups: phenyl, biphenyl, methyl, ethyl, tert-butyl, or one or more thereof;
[0035] A1-A8 are each independently selected from deuterium or phenyl, and not all of A1-A8 are deuterium;
[0036] n is an integer from 0 to 6.
[0037] Preferably, Ar is selected from the following substituted or unsubstituted groups: phenyl, biphenyl, and the substituent of Ar is one or more of the following groups which are deuterated, deuterated or undeuterated: phenyl, biphenyl;
[0038] R is independently selected from one or more of hydrogen, deuterium, fluorine, cyano, methyl, ethyl, tert-butyl, phenyl, and deuterated phenyl;
[0039] A1-A8 are each independently selected from deuterium or phenyl, and not all of A1-A8 are deuterium;
[0040] n is an integer from 0 to 6.
[0041] More preferably, Ar is selected from phenyl, biphenyl, deuterated phenyl, deuterated biphenyl;
[0042] R is independently selected from one or more of hydrogen, deuterium, fluorine, cyano, and methyl;
[0043] A1-A8 are each independently selected from deuterium or phenyl, and not all of A1-A8 are deuterium;
[0044] n is an integer from 0 to 6.
[0045] In a preferred embodiment, the compound of the present invention is any one of the following compounds:
[0046] .
[0047] An organic electroluminescent device comprises a first electrode, a second electrode and an organic layer formed between the first electrode and the second electrode; wherein the organic layer contains the compound of the present invention.
[0048] Furthermore, the organic layer comprises a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, and an electron injection layer; wherein the light-emitting layer contains the compound of the present invention.
[0049] Furthermore, the light-emitting layer contains a light-emitting host material, which is a mixture of the compound of the present invention and any one or more of compounds P-1 to P-78. Compounds P-1 to P-78 are as follows:
[0050] .
[0051] An electronic display device containing the organic electroluminescent device of the present invention.
[0052] An OLED lighting device comprising the organic electroluminescent device of the present invention.
[0053] The room temperature described in the present invention is 25±5°C.
[0054] Beneficial effects of the present invention:
[0055] The present invention designs a new type of organic electroluminescent material, which has the following excellent properties:
[0056] 1. Deuteration of active sites improves the chemical stability, photoelectric stability and thermal stability of the compound, improves the stability of the device, and thus increases its lifespan.
[0057] 2. It can form a good Premix material with the P-type compound of the present invention, has good P / N stability and mass production stability during the evaporation process, and the formed Premix material has a more balanced carrier mobility, thereby greatly improving the efficiency and life of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 A schematic diagram of the structure of an organic electroluminescent device provided by the present invention;
[0059] The numbers in the figure represent: 1-anode, 2-hole injection layer, 3-hole transport layer, 4-electron blocking layer, 5-light-emitting layer, 6-hole blocking layer, 7-electron transport layer, 8-electron injection layer, 9-cathode;
[0060] Figure 2 is the HPLC chart of compound 11 prepared in Example 1 of the present invention;
[0061] Figure 3 is the DSC spectrum of compound 11 prepared in Example 1 of the present invention, Figure 3 It can be seen that the melting point temperature Tm value of compound 11 is 292.15°C;
[0062] Figure 4 is the TGA spectrum of compound 11 prepared in Example 1 of the present invention, Figure 4 It can be seen that the thermal weight loss temperature Td value is 488.82℃; DETAILED DESCRIPTION
[0063] The following further illustrates and describes embodiments of various aspects. It should be understood that the description herein is not intended to limit the claims to the specific aspects described. On the contrary, it is intended to cover substitutions, modifications and equivalents that may be included in the spirit and scope of the present disclosure defined by the appended claims.
[0064] As used herein, in "substituted" or "unsubstituted", the term "substituted" means that at least one hydrogen in the group is re-coordinated with deuterium, a hydrocarbon group, a hydrocarbon derivative group, a halogen, or a cyano group (-CN). The term "unsubstituted" means that at least one hydrogen in the group is not re-coordinated with deuterium, a hydrocarbon group, a hydrocarbon derivative group, a halogen, or a cyano group (-CN). Examples of hydrocarbon groups or hydrocarbon derivative groups may include C1 to C30 alkyl, C2 to C30 alkenyl, C2 to C30 alkynyl, C6 to C30 aryl, C5 to C30 heteroaryl, C1 to C30 alkylamino, C6 to C30 arylamino, C6 to C30 heteroarylamino, C6 to C30 arylheteroarylamino, etc., but are not limited thereto.
[0065] Deuterium in the present invention refers to a stable isotope of hydrogen, also known as heavy hydrogen, and its element symbol is D.
[0066] As used herein, in "deuterated" or "undeuterated", the term "deuterated" means that at least one hydrogen in the group is re-coordinated with deuterium. The term "undeuterated" means that all hydrogens in the group are not re-coordinated with deuterium.
[0067] n is an integer of 0-6, which means n can be 0, 1, 2, 3, 4, 5, or 6.
[0068] The aromatic group in the present invention refers to an all-carbon monocyclic or condensed polycyclic group of 6 to 30 carbon atoms, having a completely conjugated π electron system. Non-limiting examples of aromatic groups include phenyl, naphthyl, anthracenyl, biphenyl, o-terphenyl, m-terphenyl, p-terphenyl, triphenyl[1,12-bcd]furanyl, phenanthrenyl, and the like.
[0069] The “heteroaryl group” herein refers to a heteroaryl group obtained by replacing one or more C atoms in the structure of the “aryl group” with one or more heteroatoms (such as N, O or S).
[0070] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0071] Embodiment 1:
[0072]
[0073] The synthesis method of compound 11 is as follows:
[0074]
[0075] 1-a (100 g, 0.395 mol, 1 eq), 1-b (50.6 g, 0.415 mol, 1.05 eq), potassium carbonate (109.2 g, 0.79 mol, 2 eq) and toluene / ethanol / water (1000 ml + 500 ml + 300 ml) were added to a 2L three-necked flask. Tetrakistriphenylphosphine palladium (9.13 g, 7.9 mmol, 0.02 eq) was added under N2 protection. The mixture was stirred under reflux and the reaction was carried out. HPLC monitored 1-a ≤ 1%. The reaction was stopped, water was added and stirred to separate the liquids. The aqueous phase was extracted with DCM, the organic phases were combined, dried over anhydrous sodium sulfate, filtered through silica gel, the filtrate was concentrated to dryness, 100 ml of ethanol was added and stirred to crystallize, filtered, and the filter cake was dried at 85 ° C with air blast to obtain 84.6 g of gray solid 1-c with a yield of 85.6%.
[0076]
[0077] Under N2 protection, add 1-c (84.6 g, 0.338 mol, 1 eq) and ultra-dry THF (800 ml) to a 2L three-necked flask, cool to below -20°C, add 1.6M n-butyl lithium (222 ml, 0.355 mol, 1.05 eq) dropwise, stir for 1 h, and set aside. Under N2 protection, add 1-c (234.3 g, 1.014 mol, 3 eq) and ultra-dry THF (1200 ml) to a 3L three-necked flask, cool to below -20°C, add the lithium salt solution of 1-c dropwise, and stir at room temperature for 10-18 h. Stop the reaction, cool to below 0°C, slowly add 50% ammonium chloride aqueous solution to quench, filter with suction, rinse the filter cake with ethanol 3-4 times, dry the filter cake, recrystallize it twice with o-dichlorobenzene, filter with suction, rinse the filter cake with ethanol, and dry the filter cake at 85°C to obtain 75.37 g of off-white solid 1-e with a yield of 56%.
[0078]
[0079] Under N2 protection, 1-e (75g, 0.188mol, 2eq), 1-f (11.93g, 0.094mol, 1eq), potassium carbonate (19.5g, 0.141mol, 1.5eq) and toluene / ethanol / water (750ml+375ml+225ml) were added to a 2L three-necked flask. Under N2 protection, tetrakistriphenylphosphine palladium (2.17g, 1.88mmol, 0.02eq) was added, and the temperature was raised to 70°C and stirred for 8-12h. The reaction was stopped, the temperature was lowered to room temperature, and the filter cake was filtered, and the filter cake was rinsed with water and ethanol. After the filter cake was dried, it was recrystallized twice with o-dichlorobenzene, filtered, and the filter cake was rinsed with ethanol. The filter cake was dried at 85°C with air blast to obtain 21.4g of off-white solid 1-g, with a yield of 51.2%.
[0080]
[0081] Under N2 protection, 1-h (45g, 0.159mol, 1eq), deuterated water (63.6g, 3.18mol, 20eq), trifluoromethanesulfonic anhydride (224.2g, 0.795mol, 5eq) and 1,4-dioxane (270ml) were added to a 1L three-necked flask, and the temperature was raised to 110°C and stirred for 24h. The reaction was stopped, cooled to room temperature, 500ml of water was added, filtered, the filter cake was rinsed with ethanol, and 42g of gray solid was obtained after the filter cake was dried. Deuteration was performed again under the above conditions, and post-treatment was performed to finally obtain 38g of gray solid 1-i with a yield of 82.6%.
[0082] 1-i (38 g, 0.131 mol, 1 eq), bis(boronic acid) (43.3 g, 0.171 mol, 1.3 eq), potassium acetate (38.6 g, 0.394 mol, 3 eq), XPhos (3.75 g, 7.86 mmol, 0.06 eq), Pd2(dba)3 (3.6 g, 3.93 mmol, 0.03 eq) and 1,4-dioxane (400 ml) were added to a 500 ml three-necked flask. The mixture was heated to 90-100 °C and stirred for reaction under N2 protection. HPLC monitored 1-i ≤ 0.5%. The reaction was stopped and the mixture was filtered through silica gel while hot. The filter cake was rinsed with 300 ml DCM, filtered and concentrated to dryness under reduced pressure. 100 ml ethanol was added for crystallization, filtered, and the filter cake was dried at 85 °C to obtain 33.2 g of gray solid 1-j with a yield of 66.4%.
[0083]
[0084] 1-g (21.4 g, 48.1 mmol, 1 eq), 1-j (20.2 g, 52.9 mmol, 1.1 eq), potassium carbonate (13.3 g, 96.2 mmol, 2 eq) and THF / water (660 ml + 110 ml) were added to a 1 L three-necked flask. Tetrakistriphenylphosphine palladium (1.11 g, 0.962 mmol, 0.02 eq) was added under N2 protection. The mixture was heated to 75 °C and stirred under reflux for 10-16 h. HPLC monitoring showed that 1-g was ≤ 2%. The reaction was stopped, the mixture was filtered while hot, the filter cake was rinsed with water and ethanol, the filter cake was dried at 85 °C by air blast, the filter cake was recrystallized from o-dichlorobenzene 5 times, filtered, the filter cake was rinsed with ethanol, and the filter cake was dried at 85 °C by air blast to obtain 21 g of compound 11 with a yield of 65.8%.
[0085] The following compounds were obtained in a similar manner:
[0086] Table 1-1
[0087]
[0088] Table 1-2
[0089]
[0090] Table 1-3
[0091]
[0092] Table 1-4
[0093]
[0094] Table 1-5
[0095]
[0096] Table 1-6
[0097]
[0098] Table 1-7
[0099]
[0100] Table 1-8
[0101]
[0102] The synthetic identification results of the compounds prepared above are shown in Table 2 below:
[0103] Table 2
[0104] Compound FD-Quality Compound FD-Quality 1 m / z=662.91(C45H5D23N4O=663.37) 38 m / z=660.21(C45H8D20N4O=660.35) 3 m / z=662.90(C45H5D23N4O=663.37) 40 m / z=660.18(C45H8D20N4O=660.35) 4 m / z=658.12(C45H10D18N4O=658.34) 46 m / z=660.19(C45H8D20N4O=660.35) 9 m / z=738.08(C51H10D22N4O=738.40) 47 m / z=654.87(C45H13D15N4O=655.32) 10 m / z=658.16(C45H10D18N4O=658.34) 49 m / z=660.13(C45H8D20N4O=660.35) 11 m / z=662.84(C45H5D23N4O=663.37) 56 m / z=660.12(C45H8D20N4O=660.35) 13 m / z=662.86(C45H5D23N4O=663.37) 58 m / z=660.20(C45H8D20N4O=660.35) 15 m / z=738.28(C51H10D22N4O=738.40) 65 m / z=660.14(C45H8D20N4O=660.35) 19 m / z=652.06(C45H16D12N4O=652.30) 74 m / z=678.89(C45H5D23N4S=679.35) 21 m / z=652.14(C45H16D12N4O=652.30) 83 m / z=678.86(C45H5D23N4S=679.35) 22 m / z=656.85(C45H11D17N4O=657.33) 87 m / z=742.87(C51H5D27N4O=743.43) 28 m / z=652.03(C45H16D12N4O= 652.30) 95 m / z=730.21(C51H18D14N4O=730.35) 29 m / z=656.86(C45H11D17N4O=657.33)
[0105] Device performance test:
[0106] The thermal weight loss temperature Td and melting point temperature Tm of compounds 1, 3, 4, 9, 10, 11, 13, 15, 19, 21, 22, 28, 29, 38, 40, 46, 47, 49, 56, 58, 65, 74, 83, 87, and 95 in Examples 1 to 25 of the present invention were tested. The results are shown in Table 3:
[0107] Note: Thermogravimetric temperature Td is the temperature at which the weight loss is 5% in a nitrogen atmosphere, and is measured on a TGA N-1000 thermogravimetric analyzer with a nitrogen flow rate of 10 mL / min. Tm (melting point) is measured by differential scanning calorimetry (DSC, Shinco DSC N-650) with a heating rate of 10°C / min.
[0108] Table 3:
[0109] Test material (compound) Td (℃) Tm(℃) Test material (compound) Td (℃) Tm(℃) 1 486.21 284.67 38 479.21 293.35 3 495.01 289.41 40 476.25 283.47 4 472.43 264.52 46 479.41 304.54 9 485.31 272.74 47 486.77 286.34 10 486.17 288.34 49 489.25 290.36 11 488.82 292.15 56 498.32 312.01 13 492.18 304.12 58 491.34 294.51 15 478.29 293.45 65 476.24 294.25 19 482.44 305.78 74 496.27 299.12 21 489.27 296.41 83 478.54 305.47 22 479.36 305.10 87 481.54 293.45 28 502.14 297.50 95 498.63 287.35 29 486.29 279.64
[0110] As can be seen from Table 3 above, the compounds of the present invention have relatively high Td and Tm values, indicating that they have excellent thermal stability. Applying them to organic electroluminescent devices can effectively extend the service life of the organic electroluminescent devices and obtain better use effects.
[0111] Device performance test:
[0112] Application Example 1:
[0113] ITO was used as the reflective layer anode substrate material, and its surface was treated with water, acetone and N2 in sequence;
[0114] On top of the ITO anode substrate, 10 nm of HT-1 containing 3 wt% NDP-9 was deposited to form a hole injection layer (HIL);
[0115] A hole transport layer (HTL) was formed by evaporating 100 nm of HT-1 on the hole injection layer (HIL);
[0116] GP was vacuum-deposited on the hole transport layer (HTL) to form an electron blocking layer (GPL) with a thickness of 30 nm;
[0117] Compound 11 and P1 of the present invention were co-evaporated as luminescent host materials in a mass ratio of 6:4, and GD-1 was evaporated as a doping material (the amount of GD-1 was 8% of the total weight of compound 11 and P1) on the electron blocking layer (GPL) to form a luminescent layer with a thickness of 30 nm;
[0118] HB-1 was evaporated onto the light-emitting layer to obtain a hole blocking layer (HBL) with a thickness of 20 nm;
[0119] ET-1 and LiQ were co-evaporated onto the hole blocking layer (HBL) in a mass ratio of 5:5 to obtain an electron transport layer (ETL) with a thickness of 50 nm;
[0120] Magnesium (Mg) and silver (Ag) were mixed and evaporated on the electron transport layer (ETL) in a mass ratio of 9:1 to form an electron injection layer (EIL) with a thickness of 50 nm;
[0121] Thereafter, silver (Ag) is evaporated onto the electron injection layer to form a cathode with a thickness of 100 nm, and a DNTPD with a thickness of 50 nm is deposited on the cathode sealing layer. In addition, the cathode surface is sealed with a UV curable adhesive and a packaging film (seal cap) containing a dehumidifier to protect the organic electroluminescent device from being affected by oxygen or moisture in the atmosphere. Thus, an organic electroluminescent device is prepared.
[0122]
[0123] Application Example 2-25
[0124] Compounds 1, 3, 4, 9, 10, 13, 15, 19, 21, 22, 28, 29, 38, 40, 46, 47, 49, 56, 58, 65, 74, 83, 87, and 95 in embodiments 2-25 of the present invention are used to replace compound 11 in application example 1, and other parts are consistent with application example 1, thereby preparing organic electroluminescent devices of application examples 2-25.
[0125] The difference between Control Examples 1-6 and Application Example 1 is that Compounds D1 and D2 in CN112225726A, Compound D3 in CN117658999A, Compound D4 in CN112028883A, and Compounds D5 and D6 in CN118184640 A are used to replace Compound 11 in Application Example 1, and the rest is the same as Application Example 1.
[0126] The organic electroluminescent devices prepared in Application Examples 1-25 and Comparative Examples 1-6 were tested respectively, and the test results are shown in Table 4.
[0127] Table 4
[0128] Experimental Group Luminescent host material <![CDATA[Current density (mA / cm 2 ).]]> Voltage (V) Luminous efficiency (Cd / A) Emitting color Comparative Example 1 D1+P-1 10 3.62 154.3 green Comparative Example 2 D2+P-1 10 3.56 151.4 green Comparative Example 3 D3+P-1 10 3.50 167.2 green Comparative Example 4 D4+P-1 10 3.54 161.7 green Comparative Example 5 D5+P-1 10 3.59 167.1 green Comparative Example 6 D6+P-1 10 3.64 160.2 green Application Example 1 11+P-1 10 3.32 203.3 green Application Example 2 3+P-1 10 3.40 198.2 green Application Example 3 4+P-1 10 3.34 190.9 green Application Example 4 9+P-1 10 3.33 185.7 green Application Example 5 10+P-1 10 3.31 182.4 green Application Example 6 11+P-1 10 3.41 192.6 green Application Example 7 13+P-1 10 3.36 182.3 green Application Example 8 15+P-1 10 3.41 195.8 green Application Example 9 19+P-1 10 3.35 187.1 green Application Example 10 21+P-1 10 3.35 181.2 green Application Example 11 22+P-1 10 3.42 198.1 green Application Example 12 28+P-1 10 3.37 183.0 green Application Example 13 29+P-1 10 3.41 197.2 green Application Example 14 38+P-1 10 3.38 188.2 green Application Example 15 40+P-1 10 3.39 192.6 green Application Example 16 46+P-1 10 3.46 201.2 green Application Example 17 47+P-1 10 3.41 197.5 green Application Example 18 49+P-1 10 3.37 195.1 green Application Example 19 56+P-1 10 3.31 189.6 green Application Example 20 58+P-1 10 3.40 196.2 green Application Example 21 65+P-1 10 3.32 184.9 green Application Example 22 74+P-1 10 3.37 190.8 green Application Example 23 83+P-1 10 3.39 198.7 green Application Example 24 87+P-1 10 3.35 186.4 green Application Example 25 95+P-1 10 3.38 197.5 green
[0129] It can be seen from Table 4 above that the application of the compound of the present invention in an organic electroluminescent device as a main material of a light-emitting layer can improve the luminous efficiency of the organic electroluminescent device to a certain extent, reduce the starting voltage, and relatively reduce power consumption.
[0130] The organic electroluminescent devices prepared in the control examples 1-6 and the application examples 1-12 were tested for luminescence lifetime to obtain the luminescence lifetime T97% data (the time when the luminescence brightness decreases to 97% of the initial brightness). The test equipment was a TEO luminescent device lifetime test system. The results are shown in Table 5:
[0131] Table 5
[0132] Experimental Group <![CDATA[Current density (mA / cm 2 )]]> T97% Comparative Example 1 10 91% Comparative Example 2 10 93% Comparative Example 3 10 100% Comparative Example 4 10 97% Comparative Example 5 10 95% Comparative Example 6 10 90% Application Example 1 10 168% Application Example 2 10 136% Application Example 3 10 148% Application Example 4 10 143% Application Example 5 10 152% Application Example 6 10 160% Application Example 7 10 150% Application Example 8 10 137% Application Example 9 10 144% Application Example 10 10 138% Application Example 11 10 144% Application Example 12 10 143%
[0133] It can be seen from Table 5 above that when the compound of the present invention is used as the main material of the light-emitting layer and applied to an organic electroluminescent device, the service life of the prepared organic electroluminescent device is greatly improved, so it has a very broad application prospect.
Claims
1. A compound containing a nitrogen heterocyclic structure, characterized in that: Its structural formula is shown in Formula 4 and Formula 5 below: ; Y is O or S; Ar is selected from the following substituted or unsubstituted groups: phenyl, biphenyl, terphenyl, and the substituent of Ar is deuterated, deuterated or undeuterated following groups: one or more of phenyl and biphenyl; R is independently selected from hydrogen, deuterium, deuterated or undeuterated groups: one or more of phenyl and biphenyl; A1-A8 are each independently selected from deuterium or phenyl, and not all of A1-A8 are deuterium; n is an integer from 0 to 6.
2. The compound as claimed in claim 1, characterized in that Ar is selected from the following substituted or unsubstituted groups: phenyl, biphenyl, and the substituent of Ar is one or more of the following groups which are deuterated, deuterated or undeuterated: phenyl, biphenyl; R is independently selected from one or more of hydrogen, deuterium, phenyl, and deuterated phenyl; A1-A8 are each independently selected from deuterium or phenyl, and not all of A1-A8 are deuterium; n is an integer from 0 to 6.
3. The compound as claimed in claim 1, characterized in that Ar is selected from phenyl, biphenyl, deuterated phenyl, deuterated biphenyl; R is each independently selected from hydrogen or deuterium; A1-A8 are each independently selected from deuterium or phenyl, and not all of A1-A8 are deuterium; n is an integer from 0 to 6.
4. The compound according to claim 1, characterized in that The compound is any one of the following compounds: 。 5. An organic electroluminescent device, characterized in that: The invention comprises a first electrode, a second electrode and an organic layer formed between the first electrode and the second electrode; the organic layer contains the compound according to any one of claims 1 to 4.
6. The organic electroluminescent device according to claim 5, characterized in that: The organic layer comprises a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, and an electron injection layer; and the light-emitting layer contains the compound according to any one of claims 1 to 4.
7. The organic electroluminescent device according to claim 6, characterized in that: The light-emitting layer contains a light-emitting host material, and the light-emitting host material is a mixture of any one or more of the compound according to any one of claims 1 to 4 and compounds P-1 to P-78. Compounds P-1 to P-78 are as follows: 。 8. An electronic display device, characterized in that: Contains the organic electroluminescent device as claimed in claim 5.
Citation Information
Patent Citations
Compound and organic electroluminescent device
CN112028883A
Compound and organic electroluminescent device
CN112225726A
Compound for organic optoelectronic device, organic optoelectronic device, and display device
CN117658999A
Compound containing triazine, dibenzofuran and carbazole groups and organic electroluminescent device
CN118184640A
Compound, composition and organic optoelectronic device, and display device
CN110540536A